Fossil Eucharitidae and Perilampidae (Hymenoptera: Chalcidoidea) from Baltic Amber - Heraty, John M.; Darling, D. Christopher (Zootaxa, 2009)
Palaeocharis rex n. gen. and sp. (Eucharitidae: Eucharitinae) and Perilampus pisticus n. sp. (Perilampidae: Perilampinae) are described from Baltic amber. Perilampus renzii (Peñalver & Engel) is transferred to Torymidae: Palaeotorymus renzii n. comb. Palaeocharis is related to Psilocharis Heraty based on presence of one anellus, linear mandibular depression, dorsal axillular groove, free prepectus and a transverse row of hairs on the hypopygium. This fossil is unique in comparison with extant Chalcidoidea because there are two foretibial spurs instead of a single welldeveloped calcar. Perilampus pisticus is placed into the extant Perilampus micans group because the frenum and marginal rim of the scutellum are visible in dorsal view and the prepectus forms a large equilateral triangle. The phylogenetic placement of both genera is discussed based on an analysis of both a combined morphological and molecular (28S and 18S) and morphology-only matrix. Morphological characters were used from an earlier study of Eucharitidae (Heraty 2002), with some characters revised to reflect variation in Perilampinae. Baltic amber is of Eocene age, which puts the age of divergence of these families at more than 40 mya.